Integrasi Restorative Justice dalam Sistem Peradilan Pidana Indonesia: Perspektif Keadilan Pancasila - Muchlas Rastra Samara; Pujiyono; Irma Cahyaningtyas; Sumartini Dewi (Integralistik, 2026)
The criminal justice system is not solely oriented towards punishment, but also towards restitution, accountability of perpetrators, and restoration of social relations. In the Indonesian context, restorative justice (RJ) is relevant because it aligns with the values ​​of Pancasila, particularly just and civilized humanity, deliberation, and social justice. However, the implementation of RJ has not been fully optimal due to fragmented regulations, differences in standards between institutions, limited facilitators, and the risk of unequal protection for victims. This study aims to analyze RJ as a manifestation of Pancasila Justice and formulate a strategy for its integration into the Indonesian criminal justice system. The method used is normative legal research with a statutory and case approach. The results show that RJ has a sociological basis in local wisdom and customary law, as well as an increasingly strong juridical basis, particularly through Law Number 20 of 2025 concerning the Criminal Procedure Code and Law Number 1 of 2023 concerning the Criminal Code. However, this normative strengthening has not been fully followed by systematic integration in practice. The main contribution of this article lies in the Pancasila-based RJ integration model at the normative, institutional, and legal culture levels as a direction for criminal law reform that is more recovery-oriented.